All-in-one single-piece flexible solar thermoelectric generator with scissored heat rectifying p-n modules. (March 2022) - Li, Kuncai; Sun, Xu; Wang, Yizhuo; Wang, Jing; Dai, Xu; Li, Guojia; Wang, Hong
Abstract: Junctions existing in conventional thermoelectric generators (TEGs) may lower their output power by increasing the internal resistances and reduce their flexibility, especially for organic TEGs. In this paper, we reported a new junction free all-in-one single-piece (SP) solar thermoelectric generator which was scissored from a free-standing carbon nanotube thin film with patterned p/n modules. In addition, a heat-rectifying structure has been designed to increase the temperature gradient between the hot/cold side of the TEG. A high sunlight-to-electricity output power of 1709.2 nW was obtained for the SP device, which is about 4.5 times higher than that of the conventional-structure TEG (Con-TEG). The highest output power density of this SP device is about 83 times higher than that of the Con-TEG because this fully organic SP device does not contain heavy metal moieties as connectors that typically appear in the Con-TEGs. Moreover, the junction-free SP device exhibited excellent flexibility which can be bent for 1000 times without noticeable decay and fluctuations in its conductance. While the Con-TEG cracked after being bent for only 100 times. The results indicate a promising way for developing high performance flexible organic thermoelectric devices. Graphical Abstract: ga1 Highlights: Novel single-piece structure thermoelectric generator with heat rectifying structure p-n modules. Excellent bending stability and enhanced output power. Combination of solar thermal and thermoelectric functions in one device.